Predictive factors for persistence of preoperative overactive bladder symptoms after transvaginal mesh surgery in women with pelvic organ prolapse. Issue 2 (14th December 2019) - Otsuka, Atsushi; Watanabe, Kyohei; Matsushita, Yuto; Watanabe, Hiromitsu; Tamura, Keita; Motoyama, Daisuke; Ito, Toshiki; Sugiyama, Takayuki; Miyake, Hideaki
Abstract: Background: We aimed to evaluate the effect of transvaginal mesh surgery on overactive bladder symptoms in women with pelvic organ prolapse and to identify predictive factors for persistence of a preoperative overactive bladder after surgery. Materials and Methods: We retrospectively evaluated 102 patients who underwent transvaginal mesh surgery. All patients had stage 2 or greater pelvic organ prolapse accompanied by cystocele. The Overactive Bladder Symptom Score, International Prostate Symptom Score, uroflowmetry, and postvoid residual urine volume were evaluated preoperatively and 6 months postoperatively. To identify predictive factors for the persistence of a preoperative overactive bladder after surgery, preoperative parameters were statistically compared between patients with and without the persistence of preoperative overactive bladder symptoms. Receiver operator characteristic curves were generated, and the area under the curve was calculated. Results: Preoperatively, 54 women (53%) had an overactive bladder. After surgery, the symptoms disappeared in 34 (63%) and persisted in 20 (37%) women. There were no significant differences in preoperative parameters including age, body mass index, parity, or severity of pelvic organ prolapse between patients with and without persistent preoperative overactive bladder. Preoperative Overactive Bladder Symptom Score and International Prostate Symptom Score were significantly higher in patients with persistent preoperative overactive bladder symptoms. The International Prostate Symptom Score storage subscore had the highest area under the curve, with a cutoff value of 9.5. Conclusion: Transvaginal mesh surgery eliminates overactive bladder symptoms in about two‐thirds of pelvic organ prolapse patients. The preoperative International Prostate Symptom Score storage subscore was the most useful predictive factor for the persistence of preoperative overactive bladder symptoms after surgery.